ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA DALAM INVESTASI DI PASAR MODAL SYARIAH (Studi pada Mahasiswa FEB Program Studi Perbankan Syariah UNISMA) - Yusril Ihza Maulana; Moh Amin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
This study aims to determine the effect of interest, desire, and belief factors on the interest of Malang Islamic University students to invest in the Islamic capital market. This type of research is quantitative research. In this study, the samples taken were students of the Islamic banking study program at the Islamic University of Malang who had taken Islamic capital market courses, totaling 111 students. taking the number of samples using purposive sampling technique to obtain respondents. The tool used is multiple linear regression analysis using SPSS. Simultaneous test results show the independent variable has a positive and significant effect on student interest in investing in the Islamic capital market. The results of the partial test on the interest variable (X1) have no effect on student interest in investing in the Islamic capital market (Y), the Desire variable (X2) has a positive effect on student interest in investing in the Islamic capital market (Y), and the Confidence variable (X3) has an effect on student interest in investing in the Islamic capital market (Y).